Penguatan Kapasitas Petani Kopi melalui Inovasi Pengemasan, Pelabelan, dan Pemasaran Digital Berbasis Nilai Tambah Produk - Zulkarnain Lubis; Endang Sari Simanullang; Desy Astrid Anindya; Muhammad Sapi’i Dalimunthe; Alpin Risyad Ritonga (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to strengthen the capacity of coffee farmers who are members of the Mitra Sejati Jaya Cooperative through facilitation in packaging, labeling, and value-added product-based digital marketing. The program was implemented through training sessions and Focus Group Discussions (FGDs), involving 18 participants. Evaluation instruments consisted of pre-test and post-test questionnaires, which were analyzed using descriptive quantitative methods. The evaluation results showed an increase in participants’ average scores from 57.89 in the pre-test to 82.28 in the post-test, representing an improvement of 42.12%. The program generated several outputs, including high-quality packaging, a copyrighted logo design, active social media accounts, and digital marketing video content. Therefore, this community service activity proved effective in enhancing the capacity of coffee farmers through innovations in packaging, labeling, and value-added digital marketing.